Caregiver burden in primary informal caregivers of patients with head and neck cancer - Leyti Martínez Debs; Alexis Lorenzo Ruiz; María del Carmen Llantá Abreu (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: Cancer in Cuba is currently the second cause of death at all ages for being an extremely complex disease because of the various characteristics in terms of etiology, location, evolution and prognosis. In addition, it has a psychosocial connotation and a negative emotional impact not only for the patient, but also for all those people who are part of a network of social support. Objective: The objective of this research was to characterize the caregiver burden in primary caregivers of patients with head and neck cancer, hospitalized at the National Institute of Oncology and Radiobiology from December 2016 to March 2017. Materials and methods: A mixed methodology descriptive-correlational study was carried out on 100 patients who met certain inclusion criteria. An interview for the collection of the information and the Zarit Caregiver Burden Scale were applied to subject types. Informed consent of the caregivers was obtained for their participation in the study. Results: The results revealed high levels of caregiver burden. The most affected dimension was the impact of care whereas the interpersonal burden was the least damaged dimension. It was demonstrated that, to a lesser knowledge of the caregiver about the patient's illness, greater caregiver burden and interpersonal burden.  Conclusions: It was concluded that the moderate to severe level of the burden of the primary informal caregivers of the study was mainly due to the affectations in the physical and mental health, the limitations in the personal and work areas, and the existence of negative emotional states: anxiety, worry, and depressive traits. Keywords: Caregiver burden, care impact, interpersonal burden, self-efficacy expectations, primary informal caregivers, head and neck cancer.